4(2x-y)+11=8x-13

Simple and best practice solution for 4(2x-y)+11=8x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-y)+11=8x-13 equation:


Simplifying
4(2x + -1y) + 11 = 8x + -13
(2x * 4 + -1y * 4) + 11 = 8x + -13
(8x + -4y) + 11 = 8x + -13

Reorder the terms:
11 + 8x + -4y = 8x + -13

Reorder the terms:
11 + 8x + -4y = -13 + 8x

Add '-8x' to each side of the equation.
11 + 8x + -8x + -4y = -13 + 8x + -8x

Combine like terms: 8x + -8x = 0
11 + 0 + -4y = -13 + 8x + -8x
11 + -4y = -13 + 8x + -8x

Combine like terms: 8x + -8x = 0
11 + -4y = -13 + 0
11 + -4y = -13

Solving
11 + -4y = -13

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -4y = -13 + -11

Combine like terms: 11 + -11 = 0
0 + -4y = -13 + -11
-4y = -13 + -11

Combine like terms: -13 + -11 = -24
-4y = -24

Divide each side by '-4'.
y = 6

Simplifying
y = 6

See similar equations:

| 3a+5=2a+17 | | 6x+19=-30 | | 3x-9=5x+15 | | 14x-9=21+4x | | 3t+4t=51-8 | | (-5)+4=x-3 | | 3(u+3)=-6(4u-1)+9u | | (6x+40)-2x=(2x+116)-2x | | y-11=-17 | | (5x+10)-3x=(3x+36)-3x | | 6m-9=21 | | -.25x+8=12+-5 | | 3y=12x+3+39 | | ln(6y+2)-ln(y+1)=ln(2y-1) | | -7(-4w+9)-7w=7(w-7)-7 | | (X+1)(x-1)-(x-1)=0 | | (4x+18)-2x=(2x+36)-2x | | -x-10+2x=18 | | 10x-7=(-4x)+5 | | 2(s+3)=12 | | 18=7s+2a | | (7x+15)-2=(2x+70)-2 | | 10x+30+2x+18=180 | | 10=2r | | x^2+y^2-2xy+2y+1=0 | | 4sin^2(3x)=3 | | -15+10=-5y | | 4x+2=2x+4x+12 | | (8x+44)-4=(4x+76)-4 | | 3x+15+7x+5=180 | | 12x^2-84x=0 | | (2x^2+3x-8)+(5x^2-9x+2)= |

Equations solver categories